Enhanced co-production of biohydrogen and algal lipids from agricultural biomass residues in long-term operation. (October 2019) - Ren, Hong-Yu; Kong, Fanying; Zhao, Lei; Ren, Nan-Qi; Ma, Jun; Nan, Jun; Liu, Bing-Feng
Highlights: Co-production of H2 and lipids from various agricultural biomass residues was studied. Corn stalk produced more energy than corn cob, rice straw and wheat straw. Steady and efficient energy recovery was achieved in long-term operation. The energy conversion efficiency for corn stalk increased from 5.78% to 16.96%. Abstract: This study evaluates a two-stage process by dark fermentation and microalgal cultivation for hydrogen and lipid production from different agricultural biomass residues, such as corn cob, corn stalk, rice straw and wheat straw. Results indicate that corn stalk was the best fermentation feedstock for hydrogen production and the highest accumulative hydrogen volume of 762.3 mL L −1 was obtained in batch mode. Dark fermentative effluent from corn stalk was rich in acetate and butyrate, and was favorable to lipid production. The maximum algal biomass and total lipid content reached 1461.1 mg L −1 and 35.2%, respectively. Meanwhile, the energy conversion efficiency in two-stage cultivation significantly increased from 5.78% to 16.96%. The system was stable and effective in long-term operation, and the average hydrogen production rate of 811.1 mL L −1 d −1 and lipid concentration of 588.5 mg L −1 were achieved. This study provides a promising process for enhancing energy production from agricultural wastes.